Obfuscation in competitive markets - Ernst Fehr; Keyu Wu (University of Zurich, Department of Economics, 2023)
In many markets, firms make their products complex through add-on features, thus making them difficult to evaluate and compare. Does this product obfuscation lure buyers into buying overpriced products, and if so, why does competition not eliminate this practice? More generally, under which conditions can sellers enforce stable obfuscation levels in a competitive environment such that they can increase their profits at the buyers' expense? We show - based on competitive experimental markets - that add-ons that merely complicate the products render obfuscation quite fragile because buyers display an aversion against complex products. However, if add-ons are surplus-enhancing, sellers can mitigate competition via obfuscation which generates substantial profits and persistent dispersion in headline and add-on prices. Sellers anticipate that obfuscation limits the buyers' depth and breadth of search, and they exploit this by hiding unattractive product features. Therefore, even the best product in the market is priced above marginal cost and buyers persistently fail to find the best product in the market such that inferior products have a good chance of being traded. We also identify the causal impact of obfuscation opportunities on profits and price dispersion because if we remove obfuscation opportunities, overall prices quickly converge to marginal cost. Thus, surplus-enhancing obfuscation opportunities cause persistent price dispersion, facilitate stable profits and reduce buyers' share of the surplus.
Keywords: 330; Produktgestaltung; Produktdifferenzierung; Preismanagement; Wohlfahrtsanalyse; Theorie